Naturally occurring furofuran lignans: structural diversity and biological activities. Issue 9 (3rd May 2019) - Xu, Wen-Hui; Zhao, Ping; Wang, Meng; Liang, Qian
Abstract: Furofuran lignans containing the 2, 6-diaryl-3, 7-dioxabicyclo[3.3.0]octane skeleton, represent one of the major subclasses of the lignan family of natural products. Furofuran lignans feature a wide variety of structures due to different substituents at aryl groups and diverse configurations at furofuran ring. Moreover, they exhibit a wide range of significant biological activities, including antioxidant, anti-inflammatory, cytotoxic, and antimicrobial activities. This review summarizes source, phytochemistry, and biological activities of 137 natural furofuran lignans isolated from 53 species in 41 genera of 27 plant families for the last 20 years, which provides a comprehensive information for further research of these furofuran lignans as potential pharmaceutical agents. Abstract :